From Cold to Confident: Evaluating the Value of Warm-Ups in English Language Education (Raparin Journal of Humanities (RJH), 2025)
The purpose of this study is to evaluate the value of warm-up exercises in the teaching of English. The study makes use of quantitative questionnaires and interviews as instruments for data collection that are conducted in 2023 at Salahaddin University’s English Department in the College of Education in Erbil, Iraq. The purpose of the questionnaires and interviews is to find out opinions of teachers and students about the value of warm-up exercises in language learning. The results of this study showed that warm-up exercises significantly affect students’ motivation and engagement levels, as well as their language learning process. Most teachers and students who participated believed that warm-up exercises are very helpful for English language learning. Students who take part in warm-up exercises feel more comfortable, confident, and ready to participate in the learning process. The findings of this study are important for teachers because they show that incorporating warm-up exercises in lessons can help them build strong relationships with their students. Teachers can improve students’ overall language learning and create a positive learning environment by implementing warm-up exercises.